Recent advances and prospects of axial spondyloarthritis / ankylosing spondylitis treatment - Sh. F. Erdes (Современная ревматология)
Well-established and some little-known treatments of axial spondyloarthritis / ankylosing spondylitis (AS), which have appeared in recent years are discussed, also discussed are emerging trends for AS treatment.